Observation of retained austenite by electron backscatter diffraction in Austempered Ductile Cast Iron (ADI) - Marrow, T; Cetinel, H; Wardman, N; Brough, T; Bolyan, H (2000)
This paper describes the application of the electron back scatter diffraction (EBSD) technique to characterise the retained austenite in austempered ductile cast irons. Automated analysis of electron backscatter diffraction patterns can be used to determine maps of the crystal phases and the orientation of the grains in the microstructure. Conventional metallographic techniques cannot reliably identify the prior austenite grains in austempered microstructures. This can be done by EBSD analysis of the retained austenite. EBSD combines the benefits of bulk sample analysis, such as large analysed area, with the benefits normally associated with transmission electron microscopy (high resolution, crystal phase identification and orientation measurement). In parallel with X-ray diffraction, it is a useful tool for retained austenite research. The high beam intensity at small spot size of the field emission gun scanning electron microscope (FEG-SEM) also allows high-resolution observations in fine grain microstructures, such as austempered ductile cast iron. The (110)bcc//(111)fcc [111̄]bcc//[011̄]fcc Kurdjumov-Sachs orientation relationship between ferrite and austenite is demonstrated in the ausferrite matrix in a bulk sample of an austempered ductile cast iron. The use of EBSD to study the interaction between fatigue cracks and the microstructure is also described.